Why subsidize independent schools? Estimating the effect of a unique Canadian schooling model on educational attainment - Pierre Lefebvre; Philip Merrigan (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2021)
Canada is recognized as one of the top 10 countries in secondary education according to PISA results. A particularly intriguing case in this country is the large system of highly subsidized independent schools in the province of Québec where students also perform extremely well in PISA testing. This paper uses the year Canadian 2000 PISA cohort of 15-year-olds to estimate the ATT effect of independent schooling on educational attainment. We find large, positive, robust, and statistically significant effects of independent schooling on attainment. The robustness of the results to omitted variable bias is addressed through a sensitivity analysis for matching estimators.
Keywords: I20; I21; I28; 330; YITS; high school graduation; postsecondary education and professional programsenrollment and graduation; longitudinal data; treatment effect; entropy balancing